Design and fabrication of silicon glue gun - Nurul Adrina, Mohd Nasir (2012)
The objective of this project is to design and fabricate silicon glue gun for student use at Fluid Mechanic Laboratory in University Malaysia Pahang. The main problem with the current silicon glue gun unit available is they easily hardened due to inappropriate action taken by students after each use such as use plastic to cover the nozzle after usage. The purchase of silicon glue gun by the faculty is in the big unit for the restoration purpose by lab technician which can last long for two to three month for the normal use in the lab due to economical reason. This resulted in wastage of product and extra spending in purchase new units. There are three stage involves in this project. The first stage is design or sketches few concept of the advantage of silicon glue gun. Second stage is selecting the best concept design and the last stage is fabricating the selected design of silicon glue gun. The fabrication process involves are marking, cutting, drilling, riveting, assembling and finally spraying for the final touch. As a result, project objectives have been achieved. This product may less a wasted during a maintenance work and give more benefit to the instructor.